2018
DOI: 10.1186/s13104-018-3660-7
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of diabetes retinopathy and determinants of time to diabetes retinopathy among diabetes patients at Tikur Anbessa Hospital, Ethiopia: a retrospective follow up study

Abstract: ObjectiveData regarding diabetes retinopathy and associated factors are currently lacking in Ethiopia. The study aims to determine the incidence and determinants of time to diabetes retinopathy among diabetes mellitus patients at Tikur Anbessa Specialized Hospital, Addis Ababa, Ethiopia.ResultsThe incidence of diabetes retinopathy is a rapidly growing burden of disease in Ethiopia. The incidence rate of diabetes retinopathy was 2.65 (95% CI 2. 54, 4.05) per 1000 person-years observation. Moreover, 70 (18.57%, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
27
6
2

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(47 citation statements)
references
References 34 publications
12
27
6
2
Order By: Relevance
“…Hence, the average disease-free survival time for T2DM patients was 0.40 times that of T1DM patients. This finding is analogous to the studies conducted at Ayder referral hospital 41 and Tikur Anbessa Hospital 32 in Ethiopia, which found that T2DM patients had higher risk of developing DR and other microvascular complications than T1DM patients. This could be due to the fact that most of the T2DM patients are older compared to T1DM patients.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Hence, the average disease-free survival time for T2DM patients was 0.40 times that of T1DM patients. This finding is analogous to the studies conducted at Ayder referral hospital 41 and Tikur Anbessa Hospital 32 in Ethiopia, which found that T2DM patients had higher risk of developing DR and other microvascular complications than T1DM patients. This could be due to the fact that most of the T2DM patients are older compared to T1DM patients.…”
Section: Discussionsupporting
confidence: 88%
“…Similarly, the overall cumulative incidence of DR was 20.15% with 95%CI: 16.50–24.37. A similar incidence of DR was observed from studies done in Tikur Anbessa Hospital, Addis Ababa (2.65 per 1000 PM) 32 and southern parts of Ethiopia at Arbaminch General Hospital (3.6 per 100 PY) 23 and Japan (38.3/1000 PY). 33 This could be due to almost similar health service provided for the diabetic patients.…”
Section: Discussionsupporting
confidence: 81%
“…The results of this study show that the proportion of DR was 17.17% with 20 cases per 1000 year. The study showed a higher incidence of DR than studies done in Ethiopia and China (21,26). This inconsistency might be due to the difference in health care service and complication monitoring.…”
Section: Discussioncontrasting
confidence: 63%
“…To estimate survival probability of patients we consider sex as exposure based on a research conducted in Tikur Anbessa Hospital in Addis Ababa (21).Using STATA 14.1 by using power analysis for log rank test and considering Z value at 95 % confidence, Power 80% and 10% incompleteness, the sample size was 435.…”
Section: Sample Sized For Survival Outcomementioning
confidence: 99%
“…Diabetic retinopathy is one of the leading causes of blindness worldwide, and it is an emerging cause of blindness in my country. 9 With guidance from volunteer Faculty, I provided pan-retinal photocoagulation laser treatment for patients with diabetic retinopathy for the first time. At the three-month follow-up mark, the patients' diabetic retinopathy was still under control.…”
Section: Week Three: Hands-on Training In Medical Retinamentioning
confidence: 99%